Preferensi Konsumen pada Aktivitas Callback dan Telemarketing di Restoran Cepat Saji - Rida Zuraida (Bina Nusantara University, 2013)
This paper is objected to proposed a model for delivery service at fast food restaurants to measure consumer’s preferences of callback and marketing activities. The model is developed using 4C concept (customer value, customer cost, customer convenience and customer communication). The concepts that used here are supported by previous researches on restaurant related to consumer behavior, and the theories of marketing activities including marketing and communications impact. For next steps, the measurement model should be implemented to see how far the reliability of the proposed model, and what improvements can be done in order to obtain a better model. The result can be used to develop strategies of callback and telemarketing activities for delivery service at fast food restaurant, which suit as as customer expectation and company’s resources.